Assessment of Circulating Nucleic Acids in Cancer: From Current Status to Future Perspectives and Potential Clinical Applications - Cirmena, Gabriella (Cancers (Basel), 2021)
SIMPLE SUMMARY: Liquid biopsy, defined as the family of methods aimed at identifying tumor biomarkers through noninvasive analysis of body fluids, is gaining more and more interest in the clinical setting as it represents a minimally invasive and cheap approach for the screening of cancer samples of different types. Cell-free nucleic acids represent one of the most promising biomarkers obtained from liquid biopsy, with actual and potential applications for various clinical purposes. However, standardized pre-analytical procedures as well as best-practice, highly reproducible extraction processes and quality control methods are still lacking, making it difficult to support the full implementation of cell-free nucleic acids assessment in routine clinical practice. Furthermore, the clinical utility of these biomarkers still appears to be relatively limited and focused on specific purposes. In this review, we analyze pre-analytical and analytical factors concerning cell-free nucleic acids, with a focus on cell-free DNA and circulating tumor DNA, as well as their technical and clinical applications. ABSTRACT: Current approaches for cancer detection and characterization are based on radiological procedures coupled with tissue biopsies, despite relevant limitations in terms of overall accuracy and feasibility, including relevant patients’ discomfort. Liquid biopsies enable the minimally invasive collection and analysis of circulating biomarkers released from cancer cells and stroma, representing therefore a promising candidate for the substitution or integration in the current standard of care. Despite the potential, the current clinical applications of liquid biopsies are limited to a few specific purposes. The lack of standardized procedures for the pre-analytical management of body fluids samples and the detection of circulating biomarkers is one of the main factors impacting the effective advancement in the applicability of liquid biopsies to clinical practice. The aim of this work, besides depicting current methods for samples collection, storage, quality check and biomarker extraction, is to review the current techniques aimed at analyzing one of the main circulating biomarkers assessed through liquid biopsy, namely cell-free nucleic acids, with particular regard to circulating tumor DNA (ctDNA). ctDNA current and potential applications are reviewed as well.